2017
DOI: 10.1111/bjd.15199
|View full text |Cite
|
Sign up to set email alerts
|

Vitiligo and depression: a systematic review and meta‐analysis of observational studies

Abstract: Vitiligo is a common depigmenting disorder with profound psychosocial impacts. Previous observational studies have suggested a link between vitiligo and psychiatric morbidity, such as depression. However, variability in study design makes it difficult to quantify accurately the relationship between vitiligo and depression. We aimed to investigate the underlying prevalence and risk of depression among patients with vitiligo. A comprehensive search of MEDLINE, Embase and the Cochrane Library was conducted. Cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
101
1
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 44 publications
(108 reference statements)
3
101
1
11
Order By: Relevance
“…This study expands on previous studies that showed higher rates of MH disorders in persons with vitiligo compared to those without vitiligo. A meta‐analysis study pooled data on 1080 patients with vitiligo and found that at least one in four vitiligo patients were diagnosed with a form of clinical depression when using a validated screening questionnaire . A cross‐sectional study of 150 patients with vitiligo reported high prevalences of depression (34%) and anxiety (60%) .…”
Section: Discussionmentioning
confidence: 99%
“…This study expands on previous studies that showed higher rates of MH disorders in persons with vitiligo compared to those without vitiligo. A meta‐analysis study pooled data on 1080 patients with vitiligo and found that at least one in four vitiligo patients were diagnosed with a form of clinical depression when using a validated screening questionnaire . A cross‐sectional study of 150 patients with vitiligo reported high prevalences of depression (34%) and anxiety (60%) .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 1/3 of vitiligo patients were said to have reported depressive symptoms or impaired general health issues, while close to one-fourth of the given population met diagnostic criteria for clinical depression [49]. There are studies in literature suggesting that depressive symptoms might predict overall life quality [6,50].…”
Section: Introductionmentioning
confidence: 99%
“…Vitiligo is an acquired, depigmenting skin disease commonly affecting the human population without any ethnic, racial, or socioeconomic predilection; it may have a profound adverse impact on the patient's psychological state and quality of life (Lai, Yew, Kennedy, & Schwartz, ). The classification of vitiligo is important, as it helps to decide on the course of treatment and may predict the prognosis.…”
Section: Introductionmentioning
confidence: 99%